Effect of complex biopreparations on sowing qualities of soybean seeds - Biliavska, L.; Biliavskyi, Yu.; Bruchak, Ya. (Scientific Progress & Innovations, 2022)
The article provides the results of studying the yield of conditioned seeds and sowing qualities of soybean [Glycine max (L.) Merrill] varieties of Poltava breeding (“Almaz”, “Aleksandryt”, “Antratsyt”) at the pre-sowing treatment of seeds with biopreparations of complex effect. The following preparations registered in Ukraine were used: Ryzobofit, Phosphoenteryn, Biopolicide , and Flavobakteryn. The research was conducted on the farm “Hryha”, Poltava region. The soil was typical black soil. The seeds of the studied varieties were treated with biopreparations before sowing. The productivity of the varieties and the yield of conditioned seeds were determined after cleaning. Such sowing qualities as laboratory germination and weight of 1000 seeds were also analyzed. The peculiarities of interaction of the studied varieties with biopreparations of complex action were revealed. The maximum values of the studied indicators resulting from the interaction of varietybiological preparation were determined. Sowing quality seeds enables the genetic yield potential of modern soybean varieties to be effectively realized. The yield of conditioned seeds after the refinement is of great importance. It was found that the yield of conditioned seeds by the experiment variant (on average for 5 years) of the studied varieties varied differently. The highest yield of conditioned seeds of the varieties Aleksandryt and Almaz was noted in the variant A + B + C (Rizobofit + Phosphoenteryn + Biopolicide – 1.73 t/ha and 1.53 t/ha respectively. The variety Antratsyt had the maximum value of this indicator (1.69 t/ha) in the variant A + B + D (Rizobofit + Phosphoenteryn + Flavobacteryn). The highest weight of 1000 seeds of the variety Almaz was 193.4 g in the variant A + B + D. The variety Antratsyt had the highest value of this indicator in the variant A + B + C, and in the variety Aleksandryt (182.6 g) in the variants A (Rizobofit based on M-8 bacteria strain) and A + B + C. High laboratory germination of seeds (92.52–94.4 %) was recorded after treatment with bio-complex (variant A + B + C). The highest laboratory seed germination of the variety “Almaz” was in variant A + B + C and amounted to 94.4 %. The varieties “Aleksandryt” and “Antratsyt” had the highest seed germination of 92.0 % and 93.4 % in the variant A + B + D, respectively.